IMPLEMENTASI MODEL TRANSPORTASI DISTRIBUSI PRODUK VAKSIN HEPATITIS B MENGGUNAKAN METODE LEAST COST DAN MODIFIED DISTRIBUTION - Resa Lestari; Thyar Romadhon; Muchammad Fauzi (Jurnal Lebesgue : Jurnal Ilmiah Pendidikan Matematika, Matematika dan Statistika, 2021)
The transportation method is a method related to optimization model used to minimize the cost of transportation distribution. Distribution of products to various regions requires transportation costs are not small, it requires good planning in order for the availability of goods can be met. The purpose of this study, applying the transportation cost of hepatitis B vaccine distribution from PT. XYZ by using Least Cost Method as the initial solution and Modified Distribution Method (MODI) to optimize so that companies can know the cost of optimal vaccine distribution. The results showed the implementation of transportation model by PT. XYZ with the initial solution using the Least Cost Method obtained the cost of transportation distribution of Rp 45,874,100. then after the optimization of costs by using Modified distribution method the cost of transportation distribution becomes more optimal and the minimization of costs obtained to be Rp 45,767,100.